Rapid generation of the shortest generalized Dubins path in forced landing - Tian, Min; Shi, Yingjing; Li, Rui; Tlelo-Cuautle, Esteban (Zielona Góra: Uniwersytet Zielonogórski)
This paper investigates the problem of rapid shortest path generation during an aircraft`s forced landing, where the heading angle of the target point is variable. To address the minimum turning radius constraint of the aircraft, the shortest path is determined using Dubins curves. Additionally, the shortest generalized Dubins path is selected when the heading angle of the target point is not fixed.
Keywords: generalized Dubins curve; path planning; forced landing